Assessment of Peripheral and Central Auditory Processing after Treatment for Idiopathic Sudden Sensorineural Hearing Loss - Khakzand, Soheila; Maarefvand, Mohammad; Ruzbahani, Masoumeh; Tajdini, Ardavan (International Archives of Otorhinolaryngology, 2024)
Introduction When cases of idiopathic sudden sensorineural hearing loss (SSNHL) are treated successfully, most clinicians assume the normality and symmetry of the auditory processing. This assumption is based on the recovery of the detection ability on the part of the patients, but the auditory processing involves much more than detection alone. Since certain studies have suggested a possible involvement of the central auditory system during the acute phase of sudden hearing loss, the present study hypothesized that auditory processing would be asymmetric in people who have experienced sudden hearing loss.Objective To assess the physiologic and electrophysiological conditions of the cochlea and central auditory system, as well as behavioral discrimination, of three primary aspects of sound (intensity, frequency, and time) in subjects with normal ears and ears treated successfully for SSNHL.Methods The study included 19 SSNHL patients whose normal and treated ears were assessed for otoacoustic emissions, speech auditory brainstem response, intensity and pitch discrimination, and temporal resolution in a within-subject design.Results The otoacoustic emissions were poorer in the treated ears compared to the normal ears. Ear- and sex-dependent differences were observed regarding otoacoustic emissions and pitch discrimination.Conclusion The asymmetrical processing observed in the present study was not consistent with the hearing threshold values, which might suggest that the central auditory system would be affected regardless of the status of the peripheral hearing. Further experiments with larger samples, different recovery scenarios after treatment, and other assessments are required.
Keywords: sudden hearing loss; otoacoustic emission; evoked potentials; pitch perception; just-noticeable differences